Perancangan Desain Alat Press Baglog Otomatis Jamur Tiram untuk Meningkatkan Efisiensi Waktu Produksi Jamur Tiram - Achmad, Satrio Maretdika Nur; Tjahyono, Rudi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Oyster mushrooms (Pleurotus ostreatus) are one of the most commonly cultivated edible mushrooms due to their high nutritional value and relatively simple cultivation process. One crucial stage in oyster mushroom cultivation is the preparation of baglogs, which are cylindrical growing media wrapped in plastic and filled with a mixture of sawdust and other supplementary materials. The process of compacting the baglog mixture into plastic bags requires significant time and labor when done manually. Therefore, the design of this equipment aims to develop a baglog press machine to improve efficiency and consistency in the production process. Using engineering design methods such as planning and integration, this machine is designed with a mechanical system and has dimensions of 100 x 50 x 100 centimeters. It is powered by a 1 hp electric motor running at 1400 rpm, coupled with a WPX 70 1:60 gearbox to assist the pressing lever, enabling uniform pressure, speeding up the pressing process, and reducing operator fatigue. Testing results show that this press machine can reduce baglog production time by up to 50% compared to the manual method.